Will the Polish Deal Contribute to the End of the Uncontrolled Growth of Self-Employment? - Mierkiewicz, Rafał; Gajda, Mateusz (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
1 January 2022 marks the date of entering into force provisions of the Polish Order – the biggest reform of the tax system in recent years. Initially, it seemed that the new regulations were aimed at combating the uncontrolled development of self-employment, which has become a popular and misused form of gainful employment in Poland. The main task of this paper will be to answer the question whether the newly introduced regulations may become a solution preventing the so-called bogus self-employment or on the contrary, may promote self-employment among the labour market participants.